Kinetics of sugars consumption and ethanol inhibition in carob pulp fermentation by Saccharomyces cerevisiae in batch and fed-batch cultures - Lima-Costa, Maria Emília (2014)
The waste materials from the carob processing industry are a potential resource for second-generation bioethanol production. These by-products are small carob kibbles with a high content of soluble sugars (45–50%). Batch and fed-batch Saccharomyces cerevisiae fermentations of high density sugar from carob pods were analyzed in terms of the kinetics of sugars consumption and ethanol inhibition. In all the batch runs, 90–95% of the total sugar was consumed and transformed into ethanol with a yield close to the theoretical maximum (0.47–0.50 g/g), and a final ethanol concentration of 100–110 g/l. In fed-batch runs, fresh carob extract was added when glucose had been consumed. This addition and the subsequent decrease of ethanol concentrations by dilution increased the final ethanol production up to 130 g/l. It seems that invertase activity and yeast tolerance to ethanol are the main factors to be controlled in carob fermentations. The efficiency of highly concentrated carob fermentation makes it a very promising process for use in a second-generation ethanol biorefinery.